2023
DOI: 10.3390/cimb45050277
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics and Mutational Landscape of APC, HOXB13, and KRAS among Rwandan Patients with Colorectal Cancer

Abstract: Cancer research in Rwanda is estimated to be less than 1% of the total African cancer research output with limited research on colorectal cancer (CRC). Rwandan patients with CRC are young, with more females being affected than males, and most patients present with advanced disease. Considering the paucity of oncological genetic studies in this population, we investigated the mutational status of CRC tissues, focusing on the Adenomatous polyposis coli (APC), Kirsten rat sarcoma (KRAS), and Homeobox B13 (HOXB13)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
2
1
Order By: Relevance
“…Our finding that a majority of CRC patients at KFH were male contrasts with previous authors in Rwanda, who found a higher CRC incidence in female patients [ 24 26 ]. However, ‘it is in keeping’ with or ‘it supports’ previous findings in SSA of higher incidence of CRC in males, highlighting a difference between the patient populations served by different hospitals within Rwanda providing cancer care [ 3 , 4 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our finding that a majority of CRC patients at KFH were male contrasts with previous authors in Rwanda, who found a higher CRC incidence in female patients [ 24 26 ]. However, ‘it is in keeping’ with or ‘it supports’ previous findings in SSA of higher incidence of CRC in males, highlighting a difference between the patient populations served by different hospitals within Rwanda providing cancer care [ 3 , 4 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This could be because they are easier to investigate and diagnose, possibly due to being more accessible. Additionally, rectal tumours on the left side may show more symptoms, prompting patients to seek treatment earlier [ 4 , 26 ]. Therapy responses vary greatly by tumour entity and location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation